Employees’ Perception on Lifelong Learning and Job Performance: A Case of Oil Palm Estates in Bintulu, Sarawak - Ambrose, Emang (2025)
A descriptive study has been conducted amongst oil palm plantations employees’ feedback on distance learning for furthering study while working as plantation workers. The intention was to investigate career development and training provided by HRD and HRM of the oil palm estates. Based on the research problems, three study objectives were formulated and to be answered based on respondent’s feedback. Since the targeted respondents for this academic exercise were employees at oil palm estates in Bintulu Division only, a self-administered questionnaire was designated to collect the primary data from the respective respondents. The questionnaire comprised of Socio-demographic characteristics, funding and perks for distance learning, retention rate, participation and progress tracking, specialized performance appraisal tools, knowledge transfer motivation, professional development for career progression and job performance. The result presented in Chapter 4, about 75 respondents gave feedback and analyzed to answer the study objectives. The study findings show that most of the respondents claim that they faced difficulties to furthering their study via distance learning while engaged as plantations workers. The entire study constructs recorded significant relationship with job performance. During the study period, the researcher found that the limitations of the study could probably due to the very limited time frame to undergo detail research. Short period for this study to explore on many factors influenced relationship between independents and dependent while working at the oil palm estates. Fortunately, replication study could help to reduce the burden of not meeting targeted specific time given. This study could be more efficient if the timeframe is set longer with in-depth analysis. From the study findings, a number of recommendations to suggest to be adopted inline to uplifting career development in HRD and HRM which contributed to better job performance.